Phase equilibria of (Methylbenzene + Carbon dioxide + Methane) at elevated pressure: Experiment and modelling - Al,Ghafri SZ; Trusler,JPM (Journal of Supercritical Fluids, 2019)
Phase equilibria in the ternary mixture (C7H8 + CO2 + CH4) were measured at temperatures of (323.15, 373.15 and 423.15) K and pressures up to 31 MPa by means of a synthetic method in which both bubble- and dew-points were measured. The results were compared with calculations based on the SAFT-γ Mie and the Predictive Peng-Robinson (PPR-78) equations of state, both of which use group-contribution approaches for parameters estimations. At low pressures, good agreement was observed with both models but this deteriorated with increasing pressure and, in the critical region, both models over-predict the pressure. The deviations are more pronounced at the highest methane content in the ternary system and at the lowest temperature. SAFT-γ Mie is shown to generally give better agreement with experiment than PPR-78. The current work suggests that the interaction parameters between CH4 and one or more of the functional groups in methylbenzene require further refinement.